2003
DOI: 10.1046/j.1445-2197.2003.t01-1-02710.x
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the lip: is there a role for adjuvant radiotherapy in improving local control following incomplete or inadequate excision?

Abstract: Incomplete or inadequate excision of some lip cancers results in local recurrence. If re-excision is not feasible -surgeons should consider the role of adjuvant radiotherapy in improving local control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 24 publications
1
59
0
8
Order By: Relevance
“…14,15,17,18 Although lip cancer is known to be curable especially at the early stages of the disease, it has tremendous adverse individual and public health effects related to high medical costs and, in advanced or aggressive cases, lower survival rates and diminished quality of life due to devastating aesthetic and psychosocial sequel, functional impairment, and other serious consequences. 19 Reports regarding survival after lip cancers in the developing countries are rare.…”
Section: Resultsmentioning
confidence: 99%
“…14,15,17,18 Although lip cancer is known to be curable especially at the early stages of the disease, it has tremendous adverse individual and public health effects related to high medical costs and, in advanced or aggressive cases, lower survival rates and diminished quality of life due to devastating aesthetic and psychosocial sequel, functional impairment, and other serious consequences. 19 Reports regarding survival after lip cancers in the developing countries are rare.…”
Section: Resultsmentioning
confidence: 99%
“…Radiation treatment in these cases is important in order to prevent local failure [14]. One issue with PDR brachytherapy is that the patient must have a stable and non-kinking flexible tube implant for 6 days.…”
Section: Discussionmentioning
confidence: 99%
“…15,34 Indeed, several series reported improved local tumour control with the addition of radiation therapy to excision. 67,68 However, a recent systematic review of available literature showed no significant benefit of radiation therapy beyond surgery alone. 44 In practice, radiation therapy is mostly reserved for selected patients with contraindications to surgery, for palliative purposes, or as an adjunct to highrisk SCC treatment.…”
Section: Radiation Therapymentioning
confidence: 99%